Phenolic profile of grapevine cv. Tempranillo skins is affected by timing and severity of early defoliation - Moreno, Daniel; Intrigliolo, Diego S.; Vilanova, Mar; Castel, Juan R.; Gamero, Esther; Valdés, Esperanza (INIA, 2021)
Aim of study: To investigate the effects of three early leaf removal treatments on the phenolic compounds of cv. ‘Tempranillo’ (Vitis vinifera L.) grape skins. Area of study: The experiment was conducted in a vineyard located in Requena, Valencia (South-eastern Spain) over two consecutive seasons. Material and methods: Four treatments were investigated over two seasons in drip-irrigated vines: Control (C), non-defoliated and three defoliation treatment, applied at different phenological stages and intensities where all leaves from the first 6 nodes were eliminated just before flowering (ED) and at fruitset (LD). The fourth defoliation treatment was performed at the same time of ED but only the leaves facing east of the eight first nodes were removed (EED). At harvest, thirty-eight phenolic compounds were quantified by HPLC in the grape skins, including anthocyanins, flavanols, flavonols, hydroxycinnamic acids and their tartaric derivatives. Main results: A general increase of the skin phenolic compounds concentration was found in response to the defoliation treatments. The largest and more significant effects were observed for LD in 2009 with relative increases with respect to the un-defoliated vines of 14.8, 86.0, 119.0, and 75.9% for anthocyanins, flavanols, flavonols and hydroxycinnamates, respectively. On the other hand, EED did not clearly modify any polyphenolic compound. In addition, the response of phenolic families analyzed to defoliation treatments was different. Malvidine derivatives were not altered by any of the treatments, while the contents of quercetin and kaempferol derivatives and ferulic and coumaric acids, increased in both years when LD was applied. Research highlights: The defoliation effects on specific phenolic substances were dependent on timing, severity, and the season. Skin phenolic compounds increase in response to defoliation treatments and flavonols and hydroxycinnamates were the most affected families.